A randomised controlled trial on the effects of a structural education module among women with polycystic ovarian syndrome on nutrition and physical activity changes - Dashti, Sareh; Abdul Hamid, Habibah; Mohamad Saini, Suriani; Tusimin, Maiza; Ismail, Maimunah; Esfehani, Ali Jafarzadeh; Ching, Siew Mooi; Lee, Kai Wei; Ismail, Norzian; Wong, Jie Lin; Abdul Latiff, Latiffah (BioMed Central, 2022)
Background Polycystic ovarian syndrome (PCOS) is a complex metabolic, endocrine and reproductive disorder that has a huge impact on the life of women. To ascertain the effectiveness of health education module among women with PCOS.